High-density large-size grinding material as well as preparation method and application thereof

By performing surface modification of the abrasive raw materials on silane coupling agent and mixing with adhesive, high-density large-size abrasives are prepared, which solves the problems of low density and poor durability of the existing abrasives and achieves higher wear resistance and hardness.

CN119875584APending Publication Date: 2025-04-25SHENHUA RAIL & FREIGHT WAGONS TRANSPORT
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411786618.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing abrasive products have low density, resulting in poor durability and small-sized abrasive particles are prone to fall off during grinding.

Method used

High-density large-size abrasive material is prepared by modifying the surface of the silane coupling agent and mixing it with the adhesive. After pressing and curing, a high-density large-size abrasive material is prepared.

Benefits of technology

It improves the density and wear resistance of the abrasive, enhances the hardness and stability of the abrasive tool, reduces the porosity, and improves the shape and dimensional stability of the abrasive during the grinding process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a high-density large-size grinding material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) carrying out surface modification treatment on raw materials of the grinding material by using a silane coupling agent; the raw material of the grinding material is selected from grinding materials with D50 of 5-15 microns; and (2) an adhesive is mixed with the raw materials of the grinding material obtained through treatment in the step (1), then the obtained mixed material is subjected to compression molding and curing treatment, and the high-density large-size grinding material is obtained. The grinding material disclosed by the invention has relatively high density, and when the grinding material disclosed by the invention is used for preparing a grinding tool, the wear resistance and hardness of the grinding tool can be improved on the premise of ensuring that the grinding tool has a certain porosity, so that the grinding material has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of abrasive materials and grinding tools, and in particular relates to a high-density large-size abrasive material and a preparation method and application thereof. Background Art

[0002] Abrasive grains and abrasive products made of abrasive grains can be used for grinding, trimming or grinding a variety of materials and surfaces in the product manufacturing process. Most abrasive products are formed by bonding small-sized abrasive grains together with adhesives. Firstly, considering the heat dissipation of the abrasive tool and the need to discharge the grinding chips in time during the grinding process, the abrasive tool needs to have a certain porosity. However, the presence of pores will lead to a lower overall density of the abrasive tool, making the product durability of the abrasive tool poor; secondly, when the abrasive tool is directly prepared with smaller-sized abrasive grains, single-grain abrasive grains are prone to fall off during use (such as grinding process). Therefore, it is urgent to provide a high-density and large-sized abrasive and abrasive tools made from the abrasive to meet the market demand for corresponding abrasives and abrasive tools. Summary of the invention

[0003] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-density large-size abrasive and a preparation method and application thereof; the abrasive of the present invention has a relatively high density, and the use of the abrasive of the present invention to prepare abrasive tools can ensure that the abrasive tools have improved wear resistance and hardness while having a certain porosity, and have good application prospects.

[0004] The purpose of the present invention is achieved through the following technical solutions:

[0005] In a first aspect, the present invention provides a method for preparing a high-density large-size abrasive, the preparation method comprising the following steps:

[0006] (1) using a silane coupling agent to perform surface modification on the raw material of the abrasive;

[0007] (2) Mixing the adhesive with the raw material of the abrasive obtained by the treatment in step (1), and then pressing and curing the obtained mixed material to obtain a high-density large-size abrasive.

[0008] In some embodiments of the present invention, the silane coupling agent is selected from at least one of silane coupling agent KH550, silane coupling agent KH560, silane coupling agent KH570 and the like.

[0009] In some embodiments of the present invention, the raw material of the abrasive is selected from D 50 The abrasive particles are 5 to 15 μm.

[0010] In some embodiments of the present invention, the raw material of the abrasive is selected from at least one of corundum, silicon carbide, diamond, cubic boron nitride, etc., preferably selected from at least one of corundum and silicon carbide.

[0011] In some embodiments of the present invention, the surface modification treatment comprises mixing the raw material of the abrasive with a silane coupling agent and reacting them at 60 to 120° C. for 1 to 4 hours.

[0012] In some embodiments of the present invention, the silane coupling agent reagent is a silane coupling agent aqueous solution containing 40 to 60% by mass of the silane coupling agent.

[0013] In some embodiments of the present invention, the mixing mass ratio of the raw material of the abrasive to the silane coupling agent is 100:(2-10).

[0014] In the present invention, the raw material of the abrasive is modified by using a silane coupling agent to improve the surface properties of the abrasive, such as improving its compatibility with the adhesive, which may affect the formation and distribution of pores in the abrasive during the pressing and curing process; because the introduction of the silane coupling agent helps to better fill and close the tiny pores, the porosity of the abrasive can be reduced by about 3% to 10%. The silane coupling agent can also improve the interfacial bonding force between the abrasive and the adhesive, thereby improving the wear resistance of the abrasive. The abrasive prepared by using the abrasive raw material modified by the silane coupling agent can better maintain its shape and dimensional stability during the friction and wear process, and also shows higher stability in mechanical properties.

[0015] In some embodiments of the present invention, the step (1) further comprises drying and rinsing the abrasive raw material after the surface modification treatment with the silane coupling agent.

[0016] In some embodiments of the present invention, the drying is performed in a vacuum drying oven at 60-80°C.

[0017] In some embodiments of the present invention, the reagents used for flushing include water and alcohol solvents; preferably, the flushing includes first flushing with water and then flushing with an alcohol solvent; more preferably, the alcohol solvent includes any one or two of ethanol, isopropanol, etc.

[0018] In some embodiments of the present invention, the adhesive is selected from any one or more of epoxy resin, phenolic resin, polyurethane resin, acrylic resin and the like.

[0019] In some embodiments of the present invention, the mixing mass ratio of the adhesive to the raw material of the abrasive obtained by the treatment in step (1) is 1:(2-4).

[0020] In some embodiments of the present invention, the adhesive is mixed with the abrasive obtained by the treatment in step (1) in a powder form, preferably a powder with a particle size of 10 to 100 μm.

[0021] In some embodiments of the present invention, the mixing is performed in a mixer; preferably, the mixing speed is 50-500 rpm, and the mixing time is 90-150 min; more preferably, the mixing is first performed at 50-200 rpm for 30-60 min, and then at 200-500 rpm for 60-90 min.

[0022] In some embodiments of the present invention, the pressing and forming is carried out by rolling equipment, preferably by using two or more rollers on the rolling equipment and grooves engraved on the surface thereof; preferably, the grooves engraved on the surface of the roller are grooves having any one or more structures of a tetrahedron, a cube, a cuboid, a cone, a hemisphere, etc.

[0023] In some embodiments of the present invention, the grooves engraved on the surface of the drum are grooves having a regular tetrahedron structure; preferably, the regular tetrahedron is a regular tetrahedron with a side length of 300 to 500 μm.

[0024] In some embodiments of the present invention, the grooves engraved on the surface of the drum are grooves having a cubic structure; preferably, the cube is a cube with a side length of 300 to 500 μm.

[0025] In some embodiments of the present invention, the grooves engraved on the surface of the drum are grooves having a rectangular parallelepiped structure; preferably, the rectangular parallelepiped is a rectangular parallelepiped with a length and a width both selected from 300 to 500 μm.

[0026] In some embodiments of the present invention, the grooves engraved on the surface of the drum are grooves having a cone structure; preferably, the cone has a cone height and a cone base circle diameter both selected from 300 to 500 μm.

[0027] In some embodiments of the present invention, the grooves engraved on the surface of the drum are grooves having a hemispherical structure; preferably, the hemispherical structure is a hemispherical structure having a spherical diameter selected from 300 to 500 μm.

[0028] In some embodiments of the present invention, the compression molding is performed at 80-90°C.

[0029] In some embodiments of the present invention, the compression molding is performed at 80-90°C, which means that the temperature of the roller is set to 80-90°C when the compression molding is performed in a rolling device.

[0030] In some embodiments of the present invention, the curing process includes a pre-curing process and a high temperature curing process performed sequentially.

[0031] In some embodiments of the present invention, the pre-curing treatment is performed at 80-90° C.; preferably, the pre-curing treatment time is 30-60 min.

[0032] In some embodiments of the present invention, the high temperature curing treatment is performed at 120-140° C.; preferably, the high temperature curing treatment time is 60-120 min.

[0033] In some embodiments of the present invention, the preparation method comprises the following steps:

[0034] (1) Surface modification:

[0035] 1-1) adding an appropriate amount of silane coupling agent into water and stirring for 3 to 6 hours to prepare a silane coupling agent reagent containing 40 to 60% by mass of the silane coupling agent;

[0036] 1-2) adding an abrasive raw material with a D50 of 5 to 15 μm to the silane coupling agent reagent obtained in step 1-1) at a mass ratio of 100 g abrasive raw material: (2 to 10) g silane coupling agent reagent and reacting at 60 to 120° C. for 1 to 4 hours;

[0037] 1-3) After the reaction is completed, the abrasive raw materials are recovered and placed in a vacuum drying oven at 60-80°C for 2-3 hours;

[0038] 1-4) After the dried abrasive raw material in step 1-3) is naturally cooled to room temperature, the abrasive raw material is rinsed; and then the rinsed abrasive raw material is placed in a vacuum drying oven at 60-80° C. to dry the moisture; preferably, the rinsing includes first rinsing with water and then rinsing with an alcohol solvent; more preferably, the alcohol solvent includes any one or both of ethanol and isopropanol;

[0039] (2) Pressing molding:

[0040] 2-1) adding the adhesive and the abrasive raw material obtained in step 1-4) into a mixer at a mass ratio of 1:(2-4), and mixing at 50-500 rpm for 90-150 min;

[0041] 2-2) The mixed material obtained in step 2-1) is uniformly added into a rolling device with a roller temperature set at 80-90° C., and the abrasive of corresponding shape is pressed by using the roller and the grooves on its surface;

[0042] (3) Abrasive curing:

[0043] The abrasive obtained in step 2-2) is placed in a vacuum drying oven at 80-90° C. for pre-curing for 30-60 min; then the temperature of the vacuum drying oven is raised to 120-140° C., and the temperature is maintained for 60-120 min, followed by natural cooling to room temperature to obtain the final product.

[0044] In some embodiments of the present invention, the time for drying the water in step 1-4) is 2 to 6 hours, preferably 3 to 5 hours.

[0045] In a second aspect, the present invention provides an abrasive prepared by the preparation method described in the first aspect.

[0046] In some embodiments of the present invention, the abrasive is a regular tetrahedral abrasive with a side length of 300 to 500 μm.

[0047] In a third aspect, the present invention provides a grinding tool, wherein the grinding tool is made of the abrasive material described in the second aspect.

[0048] The beneficial effects of the present invention are as follows:

[0049] The abrasive of the invention is obtained by mixing small-sized abrasive grains with an adhesive after being modified by a silane coupling agent, and then subjected to compression molding and curing treatment. First, the abrasive raw material is modified by a silane coupling agent, and the silane coupling agent is combined with hydroxyl functional groups on the surface of the abrasive and connected to the surface of the abrasive, so that the surface performance of the abrasive is improved and the compatibility between the abrasive and the adhesive is improved. The surface of the abrasive modified by the silane coupling agent can be further connected with the adhesive through the silane coupling agent to bond the abrasive together, and there are many optional types of adhesives. In the obtained large-sized abrasive product, the small-sized abrasive grains are tightly connected, and the silane coupling agent and the adhesive are connected by chemical bonds to form a network structure, so that the internal structure of the abrasive is stable, which is more conducive to obtaining an abrasive with a larger density and stronger durability.

[0050] The abrasive of the present invention is prepared by a pressing molding method. During the pressing molding process, the pore volume and the number of pores in the abrasive product can be reduced, thereby increasing the density of the abrasive product.

[0051] In the present invention, the large-sized abrasive is further subjected to a curing treatment after being pressed and formed, wherein the curing treatment includes a pre-curing treatment at a relatively low temperature and then a high-temperature curing treatment; the pre-curing treatment step can further discharge bubbles in the abrasive, thereby reducing the pores in the large-sized abrasive, thereby further improving the density of the large-sized abrasive.

[0052] The abrasive of the present invention uses resin as a bonding agent. The resin has the characteristics of high bonding strength, good plasticity, easy to obtain raw materials, low cost, etc. Moreover, when the resin-containing abrasive is used to prepare abrasive tools, the resin can further play the role of an adhesive for bonding the abrasive, thereby ensuring the strength, stability and grinding performance of the abrasive tools. The abrasive tools prepared from the resin-containing abrasives have good toughness during the grinding process, are not easy to be blocked, and have good surface quality of the processed workpiece. DETAILED DESCRIPTION

[0053] The following examples further illustrate the technology of the present invention. These examples are for illustration and example of the present invention and are not intended to limit the scope of the present invention in any form.

[0054] Example 1

[0055] A method for preparing a tetrahedral corundum abrasive, the method comprising the following steps:

[0056] (1) Surface modification:

[0057] 1-1) Take an appropriate amount of silane coupling agent KH550, add an equal amount of deionized water, and stir for 3 hours to fully hydrolyze the silane coupling agent to obtain a silane coupling agent reagent with a mass fraction of 50% of silane coupling agent KH550.

[0058] 1-2) corundum with a D50 of 10 μm was added to the silane coupling agent reagent obtained in step 1-1) at a mass ratio of 100 g corundum: 5 g silane coupling agent reagent and reacted at 90° C. for 2 h.

[0059] 1-3) After the reaction is completed, the corundum is recovered and placed in a vacuum drying oven at 70° C. for 2.5 h.

[0060] 1-4) After the dried corundum in step 1-3) is naturally cooled to room temperature, the corundum is first rinsed with distilled water and then with anhydrous ethanol to wash away the silane coupling agent attached to the surface of the corundum by physical adsorption; and then the rinsed corundum is placed in a vacuum drying oven at 70° C. for 4 hours to dry out the moisture.

[0061] (2) Regular tetrahedron forming:

[0062] 2-1) Epoxy resin powder with a particle size of 50 μm and the corundum obtained in step 1-4) were added into a mixer at a mass ratio of 1:3, and mixed at 120 rpm for 45 min, and then at 350 rpm for 75 min.

[0063] 2-2) The mixed material obtained in step 2-1) is uniformly added into a rolling device with a roller temperature set to 85° C. by a vibrating feeder, and a regular tetrahedron is pressed out using the regular tetrahedral grooves on the surface of the roller; according to actual needs, a roller with a regular tetrahedral groove with a side length of 300 μm engraved on the surface is selected to press out a regular tetrahedral abrasive with a side length of 300 μm.

[0064] (3) Abrasive curing:

[0065] The 300 μm regular tetrahedral abrasive obtained in step 2-2) was placed in a vacuum drying oven at 85° C. for pre-curing for 45 minutes; the temperature of the vacuum drying oven was then raised to 130° C. and kept warm for 90 minutes, and then naturally cooled to room temperature to obtain the final product.

[0066] The final product was sampled and the density was measured. The result showed that the density of the product was 3.5 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 4 mg / h.

[0067] Example 2

[0068] The preparation method of the abrasive is the same as that of Example 1, except that step 1-1) is: take an appropriate amount of silane coupling agent KH550, add 1.5 times the mass of deionized water, stir for 3 hours to fully hydrolyze the silane coupling agent, and obtain a silane coupling agent reagent with a mass fraction of 40% of silane coupling agent KH550.

[0069] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 5 mg / h.

[0070] Example 3

[0071] The preparation method of the abrasive is the same as that of Example 1, except that step 1-2) is as follows: corundum with a D50 of 10 μm is added to the silane coupling agent reagent obtained in step 1-1) at a mass ratio of 100 g corundum: 2 g silane coupling agent reagent and reacted at 90° C. for 2 h.

[0072] The final product was sampled and the density was measured. The result showed that the density of the product was 3.3 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 7 mg / h.

[0073] Example 4

[0074] The preparation method of the abrasive is the same as that of Example 1, except that step 1-2) is: adding corundum with a D50 of 10 μm to the silane coupling agent reagent obtained in step 1-1) at a mass ratio of 100 g corundum: 5 g silane coupling agent reagent and reacting at 60° C. for 2 h.

[0075] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 6 mg / h.

[0076] Example 5

[0077] The preparation method of the abrasive is the same as that of Example 1, except that step 1-2) is as follows: corundum with a D50 of 10 μm is added to the silane coupling agent reagent obtained in step 1-1) at a mass ratio of 100 g corundum: 5 g silane coupling agent reagent and reacted at 90° C. for 1 h.

[0078] The final product was sampled and the density was measured. The result showed that the density of the product was 3.3 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 6 mg / h.

[0079] Example 6

[0080] The method for preparing the abrasive is the same as that in Example 1, except that the temperature of the vacuum drying oven in steps 1-3) and 1-4) is 60°C.

[0081] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 5 mg / h.

[0082] Example 7

[0083] The preparation method of the abrasive is the same as that of Example 1, except that step 1-3) is as follows: after the reaction is completed, the corundum is recovered and placed in a vacuum drying oven at 70° C. for 2 h.

[0084] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 4 mg / h.

[0085] Example 8

[0086] The preparation method of the abrasive is the same as that of Example 1, except that step 1-4) is as follows: after the dried corundum in step 1-3) is naturally cooled to room temperature, the corundum is first rinsed with distilled water and then with anhydrous ethanol to wash away the silane coupling agent attached to the surface of the corundum by physical adsorption; and then the rinsed corundum is placed in a vacuum drying oven at 70° C. for 2 hours to dry the moisture.

[0087] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 5 mg / h.

[0088] Example 9

[0089] The preparation method of the abrasive is the same as that of Example 1, except that step 2-1) is: epoxy resin powder with a particle size of 20 μm and the corundum obtained in step 1-4) are added to a mixer at a mass ratio of 1:2, first mixed at 120 rpm for 45 min, and then mixed at 350 rpm for 75 min.

[0090] The final product was sampled and the density was measured. The result showed that the density of the product was 3.6 g / cm 3, the wear resistance (the ability of abrasives to resist wear) is 4 mg / h.

[0091] Example 10

[0092] The preparation method of the abrasive is the same as that of Example 1, except that step 2-1) is: epoxy resin powder with a particle size of 80 μm and the corundum obtained in step 1-4) are added to a mixer at a mass ratio of 1:3, first mixed at 120 rpm for 30 min, and then mixed at 350 rpm for 60 min.

[0093] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 6 mg / h.

[0094] Embodiment 11

[0095] The preparation method of the abrasive is the same as that of Example 1, except that step 2-2) is: the mixed material obtained in step 2-1) is evenly added into a rolling device with a roller temperature set to 80°C by a vibrating feeder, and a regular tetrahedron is pressed out using the regular tetrahedral grooves on the surface of the roller; according to actual needs, a roller with a regular tetrahedral groove with a side length of 300 μm engraved on the surface is selected to press out a regular tetrahedral abrasive with a side length of 300 μm.

[0096] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 4 mg / h.

[0097] Example 12

[0098] The preparation method of the abrasive is the same as that of Example 11, except that step (3) is as follows: placing the 300 μm regular tetrahedral abrasive obtained in step 2-2) in an 80° C. vacuum drying oven for pre-curing for 45 minutes; then raising the temperature of the vacuum drying oven to 130° C. and keeping the temperature for 90 minutes, followed by natural cooling to room temperature to obtain the final product.

[0099] The final product was sampled and the density was measured. The result showed that the density of the product was 3.3 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 5 mg / h.

[0100] Embodiment 13

[0101] The preparation method of the abrasive is the same as that of Example 1, except that step (3) is as follows: placing the 300 μm regular tetrahedral abrasive obtained in step 2-2) in a vacuum drying oven at 85° C. for pre-curing for 30 min; then raising the temperature of the vacuum drying oven to 130° C. and keeping the temperature for 90 min, followed by natural cooling to room temperature to obtain the final product.

[0102] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 4 mg / h.

[0103] Embodiment 14

[0104] The preparation method of the abrasive is the same as that of Example 1, except that step (3) is as follows: placing the 300 μm regular tetrahedral abrasive obtained in step 2-2) in a vacuum drying oven at 85° C. for pre-curing for 45 minutes; then raising the temperature of the vacuum drying oven to 120° C. and keeping the temperature for 90 minutes, and then naturally cooling to room temperature to obtain the final product.

[0105] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 5 mg / h.

[0106] Embodiment 15

[0107] The preparation method of the abrasive is the same as that of Example 1, except that step (3) is as follows: placing the 300 μm regular tetrahedral abrasive obtained in step 2-2) in a vacuum drying oven at 85° C. for pre-curing for 45 minutes; then raising the temperature of the vacuum drying oven to 130° C., maintaining the temperature for 60 minutes, and then naturally cooling to room temperature to obtain the final product.

[0108] The final product was sampled and the density was measured. The result showed that the density of the product was 3.4 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 4 mg / h.

[0109] Comparative Example 1

[0110] The preparation method of the abrasive is the same as that of Example 1, except that step (1) is not performed, that is, the preparation method comprises the following steps:

[0111] (1) Regular tetrahedron forming:

[0112] 1-1) Epoxy resin powder with a particle size of 50 μm and corundum with a D50 of 10 μm were added to a mixer at a mass ratio of 1:3, and mixed at 120 rpm for 45 min and then at 350 rpm for 75 min.

[0113] 1-2) The mixed material obtained in step 1-1) is uniformly added into a rolling device with a roller temperature set to 85° C. by a vibrating feeder, and a regular tetrahedron is pressed out using the regular tetrahedral grooves on the surface of the roller; according to actual needs, a roller with a regular tetrahedral groove with a side length of 400 μm is selected on the surface to press out a regular tetrahedral abrasive with a side length of 400 μm.

[0114] (2) Abrasive curing:

[0115] The 400 μm tetrahedral abrasive obtained in step 1-2) was placed in a vacuum drying oven at 85° C. for pre-curing for 45 minutes; the temperature of the vacuum drying oven was then raised to 130° C. and kept warm for 90 minutes, and then naturally cooled to room temperature to obtain the final product.

[0116] The final product was sampled and the density was measured. The result showed that the density of the product was 3.2 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 8 mg / h.

[0117] Comparative Example 2

[0118] The preparation method of the abrasive is the same as that of Example 1, except that epoxy resin powder is not added, that is, step 2-1) is not performed; step 2-2) is: the corundum obtained in step 1-4) is uniformly added into a rolling device with a roller temperature set to 85°C by a vibrating feeder, and a regular tetrahedron is pressed out using the regular tetrahedral grooves on the surface of the roller; according to actual needs, a roller with a regular tetrahedral groove with a side length of 300 μm engraved on the surface is selected to press out a regular tetrahedral abrasive with a side length of 300 μm.

[0119] The final product was sampled and the density was measured. The result showed that the density of the product was 3.1 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 10 mg / h.

[0120] Comparative Example 3

[0121] The method for preparing the abrasive is the same as that of Example 1, except that step (3) is not performed, and the product obtained in step 2-2) is used as the final product.

[0122] The final product was sampled and the density was measured. The result showed that the density of the product was 3.3 g / cm 3 , the wear resistance (the ability of abrasives to resist wear) is 9 mg / h.

[0123] It should be noted that the above-described embodiments are only used to explain the present invention and do not constitute any limitation of the present invention. The embodiments describe the present invention and it should be understood that the words used therein are descriptive and explanatory words, rather than limiting words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention.

Claims

1. A method for preparing high-density large-size abrasive, characterized in that: The preparation method comprises the following steps: (1) using a silane coupling agent to perform surface modification on the raw material of the abrasive; (2) Mixing the adhesive with the raw material of the abrasive obtained by the treatment in step (1), and then pressing and curing the obtained mixed material to obtain a high-density large-size abrasive.

2. The preparation method according to claim 1, characterized in that: The silane coupling agent is selected from at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570; and / or The raw material of the abrasive is selected from D 50 Abrasive particles of 5 to 15 μm; and / or The raw material of the abrasive is selected from at least one of corundum, silicon carbide, diamond, and cubic boron nitride, and is preferably selected from at least one of corundum and silicon carbide.

3. The preparation method according to claim 1 or 2, characterized in that: The surface modification treatment comprises mixing the raw material of the abrasive with a silane coupling agent and reacting at 60 to 120° C. for 1 to 4 hours; preferably, The silane coupling agent reagent is a silane coupling agent aqueous solution containing 40 to 60% by mass of the silane coupling agent; and / or The mixing mass ratio of the raw material of the abrasive to the silane coupling agent is 100:(2-10).

4. The preparation method according to any one of claims 1 to 3, characterized in that The step (1) further comprises drying and rinsing the abrasive raw material after surface modification by the silane coupling agent; preferably, The drying is carried out in a vacuum drying oven at 60-80°C; and / or The reagents used for the flushing include water and alcohol solvents; preferably, the flushing includes flushing with water first and then flushing with an alcohol solvent; more preferably, the alcohol solvent includes any one or both of ethanol and isopropanol.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The adhesive is selected from any one or more of epoxy resin, phenolic resin, polyurethane resin and acrylic resin; and / or The mixing mass ratio of the adhesive to the raw material of the abrasive obtained by the treatment in step (1) is 1:(2-4).

6. The preparation method according to any one of claims 1 to 5, characterized in that The mixing is carried out in a mixer; preferably, the mixing speed is 50-500 rpm and the mixing time is 90-150 min; more preferably, the mixing is first carried out at 50-200 rpm for 30-60 min, and then at 200-500 rpm for 60-90 min; and / or The pressing and forming is carried out by rolling equipment, preferably by using two or more rollers on the rolling equipment and grooves engraved on the surface thereof; preferably, the grooves engraved on the surface of the roller are grooves having any one or more structures of tetrahedron, cube, cuboid, cone, hemisphere, preferably grooves having a regular tetrahedron structure; more preferably, the regular tetrahedron is a regular tetrahedron with a side length of 300 to 500 μm; and / or The compression molding is performed at 80-90°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The curing process includes a pre-curing process and a high temperature curing process performed sequentially; preferably, The pre-curing treatment is carried out at 80-90° C.; preferably, the pre-curing treatment time is 30-60 min; and / or The high temperature curing treatment is carried out at 120-140° C.; preferably, the high temperature curing treatment time is 60-120 min.

8. The preparation method according to any one of claims 1 to 7, characterized in that The preparation method comprises the following steps: (1) Surface modification: 1-1) adding an appropriate amount of silane coupling agent into water and stirring for 3 to 6 hours to prepare a silane coupling agent reagent containing 40 to 60% by mass of the silane coupling agent; 1-2) adding an abrasive raw material with a D50 of 5 to 15 μm to the silane coupling agent reagent obtained in step 1-1) at a mass ratio of 100 g abrasive raw material: (2 to 10) g silane coupling agent reagent and reacting at 60 to 120° C. for 1 to 4 hours; 1-3) After the reaction is completed, the abrasive raw materials are recovered and placed in a vacuum drying oven at 60-80°C for 2-3 hours; 1-4) After the dried abrasive raw material in step 1-3) is naturally cooled to room temperature, the abrasive raw material is rinsed; and then the rinsed abrasive raw material is placed in a vacuum drying oven at 60-80° C. to dry the moisture; preferably, the rinsing includes first rinsing with water and then rinsing with an alcohol solvent; more preferably, the alcohol solvent includes any one or both of ethanol and isopropanol; (2) Pressing molding: 2-1) adding the adhesive and the abrasive raw material obtained in step 1-4) into a mixer at a mass ratio of 1:(2-4), and mixing at 50-500 rpm for 90-150 min; 2-2) The mixed material obtained in step 2-1) is uniformly added into a rolling device with a roller temperature set at 80-90° C., and the abrasive of corresponding shape is pressed by using the roller and the grooves on its surface; (3) Abrasive curing: The abrasive obtained in step 2-2) is placed in a vacuum drying oven at 80-90° C. for pre-curing for 30-60 min; then the temperature of the vacuum drying oven is raised to 120-140° C., and the temperature is maintained for 60-120 min, followed by natural cooling to room temperature to obtain the final product.

9. An abrasive prepared by the preparation method according to any one of claims 1 to 8; preferably, the abrasive is a regular tetrahedral abrasive with a side length of 300 to 500 μm.

10. A grinding tool, characterized in that: The abrasive tool is made of the abrasive material according to claim 9.

Citation Information

Patent Citations

  • High-abrasive resistance polishing grinding material and preparation method thereof

    CN101974294A

  • Multi-particle agglomeration type abrasive particles as well as preparation method and application thereof

    CN109321204A

  • Production process of superhard wear-resistant polymer abrasive

    CN113462358A

  • Method for raising wear resistance of resin diamond grinding wheel

    CN1394720A

  • Flexible bonded abrasive articles, methods of production and use

    US5250085A